(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Palliative care nursing is an essential component of healthcare aimed at enhancing the quality of life for patients with serious illnesses and their families. This article explores the multifaceted role of palliative care nurses in providing holistic support, comfort, and symptom management. Key aspects include comprehensive assessment, effective communication, personalized care planning, and support for patients and families in navigating complex healthcare decisions. Challenges such as ethical dilemmas and caregiver burden are also addressed.